Eksistensi Pemerintah Desa Menuju Entrepreneurial Government: Koperasi Merah Putih Sebagai Instrumen Pembangunan Ekonomi Masyarakat - Ismail Ismail; Parman Parman; Abdullah Abdullah (Jurnal Community, 2026)
Village governments, within a special framework of autonomy, have the authority to manage local natural resources, implement development programs, and provide public services. Juridically and normatively, villages are mandated to empower communities, encourage participation, and contribute to national development based on local wisdom. The synergy between the village government and the Merah Putih Cooperative, through the application of the concept of entrepreneurial governance, is expected to encourage community economic empowerment through cooperatives. This study aims to examine the transformation process of village government management towards entrepreneurial principles by optimizing the role of the Red and White Cooperative as an instrument for village development and community empowerment. The research method used is qualitative, with an analytical descriptive approach. The study also used a literature-based method. The findings suggest that the transformation of village governance towards entrepreneurial governance characterized by innovation, tangible results, and economic empowerment can drive adaptive and innovative governance models that prioritize community economic capacity building.